2014
DOI: 10.1007/s10967-014-3347-z
|View full text |Cite
|
Sign up to set email alerts
|

Radioiodination of 4-benzyl-1-(3-iodobenzylsulfonyl)piperidine, 4-(3-iodobenzyl)-1-(benzylsulfonyl)piperazine and their derivatives via isotopic and non-isotopic exchange reactions

Abstract: A mild and simple technique for preparing of 4-benzyl-1-(3-[ 125 I]iodobenzylsulfonyl)piperidine, 4-(3-[ 125 I] iodobenzyl)-1-(benzylsulfonyl)piperazine and their derivatives, as sigma-1 receptor ligands, with relatively high radiochemical yields via nucleophilic substitution reaction by means of isotopic and non-isotopic exchange reactions is described. Some factors affecting the radiochemical yield were commonly studied in presence of acidic medium at elevated temperature. Unfortunately, the radiochemical yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Based on these findings the authors were interested in radiolabelling the best ligand with high binding affinity and relatively good selectivity, 4-B-IBSP, with iodine-125 ( 125 I) ( Fig. 1) in order to investigate the uptake values of radiolabeled sigma ligands in target organs [17]. On the basis of the promising results of the biodistribution data of 4-benzyl-1-(3-[ 125 I]-iodobenzylsulfonyl)piperidine (4-B-[ 125 I]-IBSP) obtained from normal rats, it was concluded that this tracer may be used as an imaging agent for early detection of various cancers such as breast, prostate, liver, and lung cancers, although internal dosimetry calculations are still needed.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these findings the authors were interested in radiolabelling the best ligand with high binding affinity and relatively good selectivity, 4-B-IBSP, with iodine-125 ( 125 I) ( Fig. 1) in order to investigate the uptake values of radiolabeled sigma ligands in target organs [17]. On the basis of the promising results of the biodistribution data of 4-benzyl-1-(3-[ 125 I]-iodobenzylsulfonyl)piperidine (4-B-[ 125 I]-IBSP) obtained from normal rats, it was concluded that this tracer may be used as an imaging agent for early detection of various cancers such as breast, prostate, liver, and lung cancers, although internal dosimetry calculations are still needed.…”
Section: Introductionmentioning
confidence: 99%
“… 32 The binding principle of radionuclides to HN is that hydrogen ions near phenolic hydroxyl group of HN were replaced with the radionuclide via the nucleophilic substitution reaction. 33 Thus, the linker HN consists of a phenolic hydroxyl group and a carboxylate group to bind to radionuclides and primary NC amines, respectively. Based on the above design, two reactants were used to synthesize linker HN.…”
Section: Resultsmentioning
confidence: 99%
“…125 I-NCs were prepared using a diimide-activated amidation reaction. 33 Briefly, 5 mg of EDC and 10 mg of NHS were added into 200 μL of NCs (5.0 mg/mL) diluted with 800 μL of DI water. The mixture was stirred for 2 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation